Assessment of genetic purity of F1 progeny in Indian mustard (Brassica juncea L.) using microsatellite markers - Deepika Sharma; Manmohan Sharma; R.K. Salgotra; Punya; Anjani K. Singh (Annals of Agricultural Research, 2023)
The current research work was undertaken to identify the true to type hybrids in the F1 progeny derived from cross of RSPR-01 and Heera cultivars. Molecular characterization of parents and F1 progeny was based on the amplification pattern of single sequence repeats (SSR) markers. A total of 25 random SSR primer pairs were used for screening of parental genotypes, out of which 7 primers were found polymorphic. Three SSR primers BR_ A04_9627743, BR_ A05_25290881 and BR_ A09_3888866 were selected as the specific markers which enabled to distinguish hybrid plants from their parental lines. Six out of the seven plants confirmed their true hybrid nature as both the parental alleles were expressed. The identified specific SSR/microsatellite markers can be utilized to identify the genetic purity of hybrids and it also help in improvement of any of the parent cultivars using pedigree/backcross breeding programmes in Indian mustard.